An improvised timer for determining the value of gravitational acceleration - Millamena, Leopoldo Amabran 1949- (1979)
This study involved the making of a timer using the tuning fork, copper wire, some pieces and blocks of wood and other available materials. The results showed that the tuning fork and other materials mentioned above can be assembled or made into a timer which can determine the values of gravitational acceleration as accurately as the Atwood's machine. Trials were performed and factors as well as conditions were taken into consideration for better results like: electrical source, kind of tuning fork, values of the weights used, and the number of crests for every distance.